The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/toxins13100706
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Activity of Alkaloids in the Desert Plant Sophora alopecuroides

Abstract: Sophora alopecuroides is known to produce relatively large amounts of alkaloids; however, their ecological consequences remain unclear. In this study, we evaluated the allelopathic potential of the main alkaloids, including aloperine, matrine, oxymatrine, oxysophocarpine, sophocarpine, sophoridine, as well as their mixture both in distilled H2O and in the soil matrix. Our results revealed that all the alkaloids possessed inhibitory activity on four receiver species, i.e., Amaranthus retroflexus, Medicago sativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Given that the same product (H 2 O 2 ) of the catalyzing reaction of SOD and POD, it seems plausible that competition between the SOD and POD systems occurred relative to the generation of H 2 O 2 . Similar results were also observed in previous studies [45][46]. Thus, we speculated that VC injection could improve the anti-oxidant capability of posttransit yak through increasing the serum level of POD to regulate H 2 O 2 metabolism.…”
Section: Vc Improves the Anti-oxidant Capacity In Post-transit Yakssupporting
confidence: 90%
“…Given that the same product (H 2 O 2 ) of the catalyzing reaction of SOD and POD, it seems plausible that competition between the SOD and POD systems occurred relative to the generation of H 2 O 2 . Similar results were also observed in previous studies [45][46]. Thus, we speculated that VC injection could improve the anti-oxidant capability of posttransit yak through increasing the serum level of POD to regulate H 2 O 2 metabolism.…”
Section: Vc Improves the Anti-oxidant Capacity In Post-transit Yakssupporting
confidence: 90%
“…Oxidative stress can lead to inhibition of the photosynthesis and respiration processes, and thus, plant growth. Lei et al (2021) found that the mixture of the alkaloids from the desert plant Sophora alopecuroides significantly increased the MDA content and POD activity of Medicago sativa seedlings, whereas SOD and CAT activity of M. sativa seedlings decreased markedly. Ma et al (2020) reported that two allelochemicals benzoic acid and cinnamic acid from invasive plants reduced growth and chlorophyll content in Chrysanthemum coronarium .…”
Section: Discussionmentioning
confidence: 95%
“…Fresh leaves of B. chinensis were used to evaluate the antioxidant system, and the determination indicators mainly included the content of malondialdehyde (MDA), the activities of peroxidase (POD), catalase (CAT) and superoxide dismutase (SOD) [32]. MDA content was determined by the MDA kits (YX-W-A401, Sino Best Biological Technology Co., Ltd., Shanghai, China).…”
Section: Antioxidant System Determinationmentioning
confidence: 99%